Deportation Policy for Foreign Citizens: The Case of Eight Vietnamese Citizens in Samarinda - Aldo Sausele; Roberto Seba; Christian Fretes (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
Indonesia faces increasing challenges in immigration management due to the rising number of foreign nationals, including violations of residence permits and transnational crimes. This study aims to analyze the effectiveness of the deportation policy, focusing on the case of eight Vietnamese nationals in Samarinda. Employing a qualitative case study approach, the research involved interviews, observations, and document analysis. The population comprised all foreign nationals deported from Samarinda in 2023, with purposive sampling of eight Vietnamese individuals and key informants from relevant agencies. Data were analyzed thematically to identify patterns and factors influencing policy implementation. The results show that deportation is an effective legal instrument for addressing illegal activities and safeguarding national sovereignty, but its impact is limited by uneven local capacity and a lack of preventive measures. The conclusion highlights the need for integrated strategies, including digital surveillance, legal education, and regional cooperation, to enhance the sustainability and fairness of immigration enforcement in Indonesia.